Strategi Pengembangan Wisata Kuliner Waroeng Pohon Yogyakarta Berbasis Ecotourism - Candra Ratna Gupita (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2020)
ABSTRACTWaroeng Pohon Restaurant is a company engaged in the field of culinary in Yogyakarta culinary with traditional culinary of Central Java. This study analyzes the strategy of developing ecotourism-based Waroeng Pohon Yogyakarta culinary tourism in attracting visitors and giving visitors awareness to always love the environment. The tight competition in the culinary field makes Waroeng Pohon must have a strong strategy in order to survive and continue to exist from other culinary delights. Waroeng Pohon has a development strategy that is carried out aimed at introducing, promoting, maintaining, developing products to the community so that they can be interested in visiting Waroeng Pohon. The research method used in this research is descriptive using a case study strategy. Data collection is conducted by interview, observation, and documentation. Analysis technique which is done by collecting data, analyzing data and draw conclusion. The results of this study indicate Waroeng Pohon has a mission to be able to preserve the environment for all employees and visitors. The restaurant environment maintains environmental sustainability, with buildings that adapt to the environment. This is the Waroeng Pohon branding that sets it apart from other restaurants. This branding is the advantage of Waroeng Pohon compared to its competitors.